Acid mine drainage sludge as an alternative raw material for M-type hexaferrite preparation. (1st July 2019) - Liu, Mei; Iizuka, Atsushi; Shibata, Etsuro
Abstract: Two types of dewatered acid mine drainage sludge were sampled from abandoned Japanese mines. The sludge shows great potential to be completely reused as alternative iron and calcium sources to synthesize M-type calcium substituted barium hexaferrite with addition of BaCO3 by solid-state reaction. The precursors and as-prepared samples were investigated by X-ray diffraction (XRD), field-emission scanning electron microscopy, and thermogravimetry–mass spectroscopy. The effect of sludge addition on phase formation and microstructure evolution during calcination was discussed in details. For sludge content up to 93.9 mass % with addition of 6.1 mass % BaCO3, M-type hexaferrite can be identified in the XRD patterns of as-prepared samples calcined at 1100, 1200, and 1300 °C. The impurities in the sludge, such as silicon, and aluminum, result in formation of secondary aluminosilicates phases; another impurity sulfur in the sludge may increase M-type hexaferrite formation temperature owing to barium or calcium sulfate formation in the precursor. The impurities also contribute to the difference in the microstructure for lower melting point. Possible applications of the sludge-derived hexaferrite products such as magnetic material or microwave absorber are suggested. Graphical abstract: Image 1 Highlights: Two types of acid mine drainage sludge from Japanese mines studied. The sludge was used as alternative Fe and Ca sources to form value-added product. M-type hexaferrite can be obtained when Fe source completely replaced by sludge. Impurities in sludge affect phase composition and microstructure. Possible applications proposed for sludge-derived products.